Model Development of Extension Technique the Inquiry Discovery in Writing Letter on the Scope of the Local Government of Kabupaten Bantaeng - Abbas, Asriani (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The counselling model with inquiry discovery technique is designed with the aim of improving the ability of the government and its apparatus in implementing the standard Indonesian language in writing the official letters as a communication tool to run the government matters and development in the life of globalization.This research aims at knowing the role model of counselling techniques the inquiry discovery to the increased capacity of government officials to write letter on the scope of government offices in Kabupaten Bantaeng. The benefit of this research is the government and its officials give recognition to Indonesia language in running the system and the wheels of government in Indonesia.This research uses a model adapted from the cooperative extension model of cooperative learning (cooperative learning) which is one of the learning models of Student CanteredLearning (SCL). The learning model is oriented towards bringing together the participants to work together in small groups consisting of 4 to 6 people. The inquiry discovery is one method of learning/education that emphasizes critical thinking and analytical processes. The research data is sourced from the tests ability to write letter of administration staff government offices in Kabupaten Bantaeng which includes competence spelling, word formation, choices of words, forming sentences, and preparation of a paragraph. This research is done from August to December 2016.The results of this research show that the model of cooperative extension with inquiry discovery techniques can improve the ability of the participantsâ skill in writing letter to the scope of local government agencies in Kabupaten Bantaeng. The development of cooperative extension model with inquiry discovery technique is superior to the conventional model of education in improving the quality of writing official letter related to the application of the rules of standard language on the scope of government.